The Fire Resistance of Transformable Barriers: Influence of the Large-Scale Factor - Marina Gravit; Daria Shabunina; Oleg Nedryshkin (Fire, 2023)
The paper presents the results of the development of a multi-layer protective product, which is a transformable fire barrier, installed in buildings and structures to limit the spread of flame, heat flow and smoke. Based on the results of the simulation of eight samples of fire curtains, three promising samples of different compositions were selected, demonstrating a fire resistance limit on the loss of thermal insulating capacity (I) of 30 min. During the small-scale tests, it was found that the multilayer fabric of the following composition was promising: heat-treated silica fabric, aluminum foil, mineral fiber heat insulation material, stitched by needle-punching with silica thread, fabric reinforced with fiberglass mesh and stitched through with basalt thread, with seams treated with a fire-resistant elastic sealant. According to the results of a standard large-scale experimental study, a fire curtain with a loss of integrity not less than 60 min, and a loss of thermal insulating ability not less than 15 min were obtained. The results of the study assess the impact of the scale factor on the fire resistance limit of fire curtains in a fire.